Caracterização petrográfica, de índices físicos e da exalação de radônio em rochas ornamentais do estado do ceará, Brasil - De Azevedo, Leiliane Rufina Pereira [UNESP]; Artur, Antonio Carlos [UNESP]; Bonotto, Daniel Marcos [UNESP]; Nogueira Neto, José de Araújo (My University, 2015)
L. R. P. Azevedo, A. C. Artur, D. M. Bonotto, J. A. Nogueira Neto - Characterization of the petrography, physical indices and radon exhalation in dimensional stones of Ceará State, Brazil. This paper deals with the quantification of the radon gas exhalation in dimension stones exploited in the state of Ceará, Brazil. It has been reported tests of physical indices, mass spectrometry with inductively coupled plasma (ICP-MS), petrographic analysis and monitoring of the radon gas exhalation in 15 different types of rocks. In their mineralogical composition, the rocks have concentrations of certain radionuclides such as 232Th, 235U and 238U, which generate 220Rn, 219Rn and 222Rn, respectively, and 222Rn is the most important in this study due to its highest half-life (3.85 days), in relation to that of other radon isotopes. The Environmental Protection Agency of the United States (USEPA) recommends a limit of 4 pCi/L for the radon exhalation by rocky materials utilized as coatings in indoor environments of residences and commercial/public constructions. The rocks studied showed exhalation values ranging from 0.04 pCi/L to 2.59 pCi/L in a closed environment, which are below the maximum value proposed by the USEPA. Therefore, they are suitable as coating materials in indoor environments with low air circulation.
Characterization of the petrography, physical indices and radon exhalation in dimensional stones of Ceará State, Brazil